2014
DOI: 10.1016/j.cropro.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium soil amendments on phenolic compounds and soft rot resistance in potato tubers

Abstract: Nutrients such as boron, nitrogen and calcium stimulate the production of phenols.This research focuses on the role of calcium in increasing phenol metabolism in potato peels and the ensuing tuber resistance to soft rot pathogens was investigated.Two field experiments were conducted at the University of Zimbabwe campus plots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…In fruit trees, Ca directly affects fruit quality, softening, stability and shelf life, and low contents result in increased respiration and consequently affect fruit shelf life (Malavolta, 2006;Aular and Natale, 2013). Ca is also considered one of the most important nutrients for plants because it is associated with plant defense, and it may influence the growth, anatomy, morphology and chemical composition of crop species (Nagadze et al, 2014).…”
Section: Macronutrient Concentrations In Plant Tissuesmentioning
confidence: 99%
“…In fruit trees, Ca directly affects fruit quality, softening, stability and shelf life, and low contents result in increased respiration and consequently affect fruit shelf life (Malavolta, 2006;Aular and Natale, 2013). Ca is also considered one of the most important nutrients for plants because it is associated with plant defense, and it may influence the growth, anatomy, morphology and chemical composition of crop species (Nagadze et al, 2014).…”
Section: Macronutrient Concentrations In Plant Tissuesmentioning
confidence: 99%
“…It seems that correlation analysis could be used for tentative examination of these relations. As reported in the literature, calcium stimulates the biosynthesis of caffeic and chlorogenic acids in potato and increases the levels of enzymes involved in plant defence mechanisms [31]. It will thus be beneficial for potato growers to supplement the soil with calcium to reduce the maceration effect of pectolytic pathogens, since calcium improves tuber resistance against the pathogens.…”
Section: Pearson's Correlation Analysismentioning
confidence: 88%
“…These indicated that PC-1 (Table 1) and PC-1 (Table 3) were related to the development of the vascular bundle of grafting union. The 7 main indicators of the 17 main indicators in PC-1 (Table 1) and PC-1 (Table 3) (41%) directly were related with calcium signal [POD (Erinle et al 2016), cellulose content (Lin et al 2016), chlorogenic acid content (Ngadze et al 2014), CDPK (Fu et al 2013), CHI , GST (Dulhunty et al 2001), and BRD (Zhou et al 2004)]. Therefore, after grafting, vascular bundle development at the scion may depend on biological responses in which intracellular calcium acts as a second messenger.…”
Section: Discussionmentioning
confidence: 99%
“…PGA is converted into phosphoenolpyruvate (PEP) with entering into second metabolism (Facchinelli and Weber 2011). Calcium can increase the second metabolism, to produce the chlorogenic acid (Ngadze et al 2014), such as cinnamic acid and coumaric acid (Clifford et al 2003). Cinnamic acid was dimerized to lignans (Heinonen et al 2001), and then reduced by PCBER to other secondary metabolites, such as phytoalexins and heartwood-protective substances (Min et al 2003).…”
Section: Discussionmentioning
confidence: 99%